Ureteral stents in urolithiasis - Matthias Beysens; Thomas O. Tailly (Asian Journal of Urology)
Ever since the ureteral stent design was fitted with a curl on both sides to prevent it from migrating up or down the ureter some 40 years ago, its use has gained tremendous momentum, aiding in the rise and evolution of endourology and has confidently kept its place in modern time urology. Over the past four decades, several designs, coating and biomaterials have been developed, trying to reduce infection, encrustation and other stent related symptoms. As the ideal stent has not yet been discovered, different ways of helping patients with their complaints have been researched. This review will cover these aspects of stent use in urolithiasis. Keywords: Ureteral stent, Prosthesis, Urolithiasis, Stent-related symptom, Alpha-blocker